OPTIMASI KOORDINASI OVER CURRENT RELAY PADA TRAFO 60 MVA 150/20 KV DAN PENYULANG 20 KV GUMUL GARDU INDUK BANARAN BERBASIS PARTICLE SWARM OPTIMIZATION - Yulia Setyaningrum; Suprihadi Prasetyono; Andi Setiawan (Fakultas Teknik, Universitas Jember, 2021)
Abstract At Banaran Transformer Substation 60 MVA 150/20 kV, the problem that often occurs is a short circuit fault. Short circuit fault sometimes causes the 20 kV Gumul Feeder to go out, so that the incoming safety of the 60 MVA transformer is also affected. This is because the coordination of the relay between the 20 kV Gumul feeder OCR and the 60 MVA incoming transformer OCR is less selective in isolating the disturbance which causes the relays not to overlap (not overlap). Therefore, to improve the performance of OCR coordination, it is necessary to set optimal OCR using the PSO method. The results of this study indicate the value of the OCR setting on the feeder side using PSO produces a TMS of 0.1197 s with a relay operating time of 0.2471 s faster than the conventional results obtained by a TMS of 0.1453 s with a relay operating time of 0.300 s. So that the results of the PSO resulted in an increasing CTI of 0.3529 s, while the results from the conventional method obtained a CTI of 0.300 s. Based on these results it can be concluded that the coordination of the relay between the 20 kV Gumul Feeder OCR and the 60 MVA incoming transformer OCR can work quite selectively by isolating the disturbance appropriately. Keywords — Coordination, Short Circuit, OCR, PSO, TMS